Forms of Exile in Jewish Literature and Thought Twentieth-Century Central Europe and Migration to America - Volková, Bronislava (Academic Studies Press, 2021)
Forms of Exile in Jewish Literature and Thought deals with the concept of exile on many levels-from the literal to the metaphorical. It combines analyses of predominantly Jewish authors of Central Europe of the twentieth century who are not usually connected, including Kafka, Kraus, Levi, Lustig, Wiesel, and Frankl. It follows the typical routes that exiled writers took, from East to West and later often as far as America. The concept and forms of exile are analyzed from many different points of view and great importance is devoted especially to the forms of inner exile. In Forms of Exile in Jewish Literature and Thought, Bronislava Volková, an exile herself and thus intimately familiar with the topic through her own experience, develops a unique typology of exile that will enrich the field of intellectual and literary history of twentieth-century Europe and America.